Efficacy and safety of extended duration letermovir prophylaxis in recipients of haematopoietic stem-cell transplantation at risk of cytomegalovirus infection: a multicentre, randomised, double-blind, placebo-controlled, phase 3 trial - Russo, Domenico; Schmitt, Michael; Pilorge, Sylvain; Stelljes, Matthias; Kawakita, Toshiro; Teal, Valerie L.; Haber, Barbara; Bopp, Charlene; Dadwal, Sanjeet S.; Badshah, Cyrus (The lancet. Haematology, 2024)
BACKGROUND: In a pivotal phase 3 trial of cytomegalovirus prophylaxis with letermovir for up to 100 days after allogeneic haematopoietic stem-cell transplantation (HSCT), 12% of participants developed clinically significant cytomegalovirus infection after letermovir was discontinued. We aimed to evaluate the efficacy and safety of extending the duration of letermovir prophylaxis for clinically significant cytomegalovirus infection from 100 days to 200 days following HSCT. - METHODS: We conducted a multicentre, randomised, double-blind, placebo-controlled, phase 3 trial at 32 sites in six countries (France, Germany, Italy, Japan, the UK, and the USA). Cytomegalovirus‑seropositive HSCT recipients (aged ≥18 years) who had received letermovir prophylaxis for up to 100 days following HSCT and who remained at high risk of late clinically significant cytomegalovirus infection (with no previous history of clinically significant cytomegalovirus infection, defined as initiation of pre-emptive therapy for documented cytomegalovirus viraemia, onset of cytomegalovirus end-organ disease, or both) were eligible. Participants were randomly assigned (2:1) to receive either an additional 100 days (ie, a total of 200 days; letermovir group) of oral or intravenous letermovir 480 mg once daily, adjusted to 240 mg once daily for participants on cyclosporin A, or 100 days of a placebo comparator for letermovir (ie, a total of 100 days of letermovir; placebo group), following HSCT. Randomisation was done using a central interactive response technology system, stratified by study centre and haploidentical donor (yes or no). Participants, investigators, and sponsor personnel were masked to the treatment allocation. The primary efficacy endpoint was the proportion of participants from randomisation to week 28 (200 days after HSCT) with clinically significant cytomegalovirus infection, analysed using the full analysis set population (ie, those who received at least one dose of study intervention). Safety was analysed in all participants as treated (ie, those who received at least one dose according to the study intervention they were assigned to). This study is registered with ClinicalTrials.gov, NCT03930615, and is complete. - FINDINGS: Between June 21, 2019, and March 16, 2022, 255 patients were screened for eligibility and 220 (86%) were randomly assigned (145 [66%] in the letermovir group and 75 [34%] in the placebo group). Between randomisation and week 28, four (3%) of 144 participants in the letermovir group and 14 (19%) of 74 in the placebo group developed clinically significant cytomegalovirus infection (treatment difference -16·1% [95% CI -25·8 to -6·5]; p=0·0005). The most common adverse events among participants in the letermovir group versus the placebo group were graft-versus-host disease (43 [30%] vs 23 [31%]), diarrhoea (17 [12%] vs nine [12%]), nausea (16 [11%] vs 13 [18%]), pyrexia (13 [9%] vs nine [12%]), and decreased appetite (six [4%] vs nine [12%]). The most frequently reported serious adverse events were recurrent acute myeloid leukaemia (six [4%] vs none) and pneumonia (three [2%] vs two [3%]). No deaths were considered to be drug-related by the investigator. - INTERPRETATION: Extending the duration of letermovir prophylaxis to 200 days following HSCT is efficacious and safe in reducing the incidence of late clinically significant cytomegalovirus infection in patients at risk. - FUNDING: Merck Sharp & Dohme LLC.